Youth Decision-Making and Crime: Influences of Stressful Conditions, Adverse Mental and Physical States, and Conventional Activities - Timmer, Anastasiia (Crime & delinquency, 2024)
This study focuses on sources of youth decision-making and examines paths through which these factors may affect delinquent behavior. Using longitudinal Add Health data, we explore the mediating mechanisms linking several antecedents of decision-making, thoughtfully reflective decision-making (TRDM), and crime. We find that various adverse factors (i.e., family and school stressful conditions, depression, sleep problems) reduce the ability of adolescents to be thoughtful and reflective, which leads to higher levels of criminal behavior. By contrast, involvement in conventional activities (i.e., hobbies, religious activities) is found to foster TRDM, which reduces delinquency. Our study calls for an integration of perspectives in criminology, cognitive psychology, and neuroscience to better explain the relationship between decision-making and crime. Policy implications are discussed.